Why are child poverty rates higher in Britain than in Germany? A longitudinal perspective - Stephen P. Jenkins; Christian Schluter (University of Essex, Institute for Social and Economic Research (ISER), 2001)
We analyse why child poverty rates were much higher in Britain than in Western Germany during the 1990s, using a framework that focuses on poverty transition rates. Child poverty exit rates were significantly lower, and poverty entry rates significantly higher, in Britain. We decompose these cross-national differences into differences in the prevalence of trigger event (changes from one year to the next in household composition, household labour market attachment, and labour earnings), and differences in the chances of making a poverty transition conditional on experiencing a trigger event. It is the latter which are most important in accounting for the cross-national differences in poverty exit and entry rates.
Keywords: 330